Factors Influencing Decisionsto Conduct Early Detection of Cervical Cancer - Sidabutar, Sondang; Suwandi, Tjipto; Martini, Santi; Hargono, Rachmat (Health Notions, 2018)
The Visual Inspection with Acetic Acid (VIA) is one of the methods to perform cervical cancer test by applying acetic acid. The huge number of cervical cancer cases in Indonesia has worsened because more than 80% of the cases that have been brought to hospitals were already in an advanced stage. The aim of the research is to analyse the variable influence: projection, self efficacy and intention toward the decision to perform early detection of cervical cancer with the VIA test. The research design was cross sectional. The population were women of childbearing age in Pematangsiantar and the samples size were 245 respondents selected by multistage random sampling. The variables were projection, self efficacy intention and decision. The statistical analysis was Structural Equation Modelling. The results of the study were: 1) self efficacy affects intention (p= 0.000), 2) projection affects intention (p= 0.000), 3) intention affects decision (p= 0.000). The models of projection, self efficacy and intention take effect on the decision to perform early detection of cervical cancer with the VIA. Keywords: Self efficacy, Intention, Decision, Visual Inspection with Acetic Acid